2022
DOI: 10.7759/cureus.21838
|View full text |Cite
|
Sign up to set email alerts
|

Variation in COVID-19 Disease Severity and Clinical Outcomes Between Different ABO Blood Groups

Abstract: The primary objective of this study was to explore whether coronavirus disease 2019 severity and outcomes varied between different ABO blood groups. This retrospective study included 363 COVID-19 confirmed patients who had their blood group recorded in the hospital medical records, from March to June 2020. Data representing demographics, clinical features, vital signs, laboratory findings, and COVID-19 outcomes were collected. Multivariate logistic regression was used for analysis and the results were adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our study first demonstrates that ABO blood groups alone do not have an influence on COVID-19 mortality ( P =0.405). This is consistent with the observations of several studies [ 5 , 8 , 12 , 17 , 21 ]. However, the results of many studies are inconsistent regarding ABO blood groups and their associations with COVID-19 severity, as some studies suggest a relationship between ABO blood type and mortality, while others do not.…”
Section: Discussionsupporting
confidence: 94%
“…Our study first demonstrates that ABO blood groups alone do not have an influence on COVID-19 mortality ( P =0.405). This is consistent with the observations of several studies [ 5 , 8 , 12 , 17 , 21 ]. However, the results of many studies are inconsistent regarding ABO blood groups and their associations with COVID-19 severity, as some studies suggest a relationship between ABO blood type and mortality, while others do not.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with the study done by Jawdat et al in Saudi Arabia, which concluded that blood group phenotype B is a risk factor for COVID-19 disease, 16 On the contrary; Jiao Zhao et al found that blood group A was associated with an increased risk, whereas blood group O was associated with a decreased risk. 9 A similar study done in India in 2021 revealed that A, B, and RhD positive were found to be more susceptible to COVID-19 infection, whereas blood groups O, AB, and RhD negative were at a lower risk of COVID-19 infection, and no association was found between blood groups and susceptibility to the severity of disease and mortality in this study 25 In Table 4, we summarize other studies from Saudi Arabia that contained a control group (or used historic control data), 20,24,[26][27][28][29][30][31] focusing on blood group association with COVID-19 vulnerability and disease severity. We did not include two studies that lacked a proper control group or detailed statistical analysis.…”
Section: Discussionmentioning
confidence: 91%
“…In Table 4, we summarize other studies from Saudi Arabia that contained a control group (or used historic control data), 20,24,26–31 focusing on blood group association with COVID‐19 vulnerability and disease severity. We did not include two studies that lacked a proper control group or detailed statistical analysis 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported no association between ABO blood types and severe COVID-19 outcomes but in accordance with the finds reported for the risk of infection [ 19 , 20 , 60 , 65 , 67 ]. Further studies also failed to report any association between the ABO blood group and severe COVID-19 outcomes [ [79] , [80] , [81] , [82] ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%